Factores relacionados con el rendimiento académico en estudiantes de Medicina Veterinaria - Pizarro R., Sara (2021)
A research work was carried out with veterinary medicine students from two universities in Lima, Peru, to determine factors that influence academic performance and the relationship between family functioning and academic performance. For this, 392 students were randomly surveyed (173 from the Universidad Nacional Mayor de San Marcos and 219 from the Universidad Científica del Sur). For data collection, a 20-question survey was applied based on the Family Cohesion and Adaptability Assessment Scale (FACES III). The results showed that the final average grades of the courses of the total population of students ranged from 12.9 to 13.2, with passing grades in both universities. Academic performance did not have a significant relationship with family types according to Olson's Circumflex Model; however, it was possible to establish significant differences in the final averages of the grades depending on the university of origin, academic year and by category, which are the result of the combinations between cohesion and adaptability. It can be concluded that family functioning is not related to the academic performance of the university students of the two universities.